The ERA Registry Annual Report 2020: a summary - Astley, Megan E; Boenink, Rianne; Abd ElHafeez, Samar; Trujillo-Alemán, Sara; Arribas, Federico; Åsberg, Anders; Beckerman, Pazit; Bell, Samira; Bouzas-Caamaño, María Encarnación; Farnés, Jordi Comas; Galvão, Ana Amélia; Gjorgjievski, Nikola; et al. (Oxford University Press (OUP), 2023)
The European Renal Association (ERA) Registry collects data on kidney replacement therapy (KRT) in patients with ESKD. This paper is a summary of the ERA Registry Annual Report 2020, also including comparisons among primary renal disease (PRD) groups. Methods Data were collected from 52 national and regional registries from 34 European countries and countries bordering the Mediterranean Sea: 35 registries from 18 countries providing individual level data and 17 registries from 17 countries providing aggregated data. Using this data, KRT incidence and prevalence, kidney transplantation rates, expected remaining lifetimes and survival probabilities were calculated. Results A general population of 654.9 million people was covered by the ERA Registry in 2020. The overall incidence of KRT was 128 per million population (p.m.p.). In incident KRT patients, 54% were older than 65 years, 63% were men and the most common PRD was diabetes mellitus (21%). Regarding initial treatment modality in incident patients, 85% received haemodialysis (HD), 11% received peritoneal dialysis (PD) and 4% received a pre-emptive kidney transplant. On 31 December 2020, the prevalence of KRT was 931 p.m.p. In prevalent patients, 45% were older than 65 years, 60% were men and glomerulonephritis was the most common PRD (18%). Of these patients, 58% were on HD, 5% on PD and 37% were living with a kidney transplant. The overall kidney transplantation rate in 2020 was 28 p.m.p., with a majority of kidney grafts from deceased donors (71%). The unadjusted 5-year survival, based on incident dialysis patient from 2011–15, was 41.8%. For patients having received a deceased donor transplant, the unadjusted 5-year survival probability was 86.2% and for patients having received a living donor transplant it was 94.4%. When comparing data by PRD group, differences were found regarding the distribution of age groups, sex and treatment modality received.